Exploring SAVE Farm’s online presence: a qualitative content and sentiment analysis - Johnson, Kennedy Chanel (My University, 2025)
As veterans return to civilian life, and more are seeking career paths in agriculture, the demand for training programs continues to grow. The Servicemember Agricultural Vocation Education Farm (SAVE Farm), located in Manhattan, KS, is an organization that offers programs designed to help veterans and servicemembers gain certification in agricultural skills, preparing them for careers on farms and ranches. Research on the marketing efforts of veteran-focused agricultural training programs remains limited, particularly in the case of the SAVE Farm program. Social media is a widely used tool for businesses and organizations to promote their services or products. Exploring how veteran-focused agricultural training programs are marketing their organization on social media to veterans can provide insight into how to better efforts to be more effective. The purpose of this study was to explore SAVE Farm’s online presence through a content analysis of their Facebook page. Additionally, a sentiment analysis for SAVE Farm was conducted through Mentionlytics. The conceptual framework guiding this study consists of the Uses and Gratifications Theory and Framing Theory. Uses and Gratifications Theory explores the reasons individuals engage with social media, focusing on the needs they seek to satisfy and gratifications they derive from their involvement. Framing Theory addresses how messages and visuals are selected and framed to shape the audience’s perception of an event, influencing how they interpret and respond to the information. The study followed a qualitative content analysis design, along with a sentiment analysis conducted through Mentionlytics. Posts from SAVE Farm’s Facebook page were collected in November 2024. These posts spanned from January 1, 2024, to October 22, 2024. These posts were examined for their visuals and captions. Codes were derived from both the imagery and captions, allowing for the identification of recurring themes. The results of the study revealed that SAVE Farm’s current social media marketing efforts primarily target a male demographic, while also striving to communicate the organization’s values through its captions. While SAVE Farm includes calls-to-actions in captions when promoting events, there is an opportunity to increase engagement by tagging collaborators and partners in the captions. These collaborations can increase awareness of both the events and SAVE Farm itself. The results also indicated that most of the sentiment surrounding online content about and posted by SAVE Farm was either positive or neutral. Future research should explore additional social media platforms where SAVE Farm is active, such as X (Twitter), Instagram and YouTube. Expanding beyond SAVE Farm, research should also examine similar programs across the United States that focus on training veterans in agricultural practices. To support the growth of agricultural programs aimed at helping veterans, it is crucial to encourage the effective use of social media in marketing these organizations.
Keywords: Agricultural training programs; Content analysis; SAVE Farm; Social media marketing; Veterans; Sentiment analysis